2016
DOI: 10.1111/jep.12562
|View full text |Cite
|
Sign up to set email alerts
|

Can we identify termination of resuscitation criteria in cardiac arrest due to drowning: results from the French national out‐of‐hospital cardiac arrest registry

Abstract: The model is helpful to highlight explanative variables concerning CAD patients' outcome. The next step is the validation of these five factors by a larger study. Prevention and public training to lifesaving behaviours must be considered as priorities in French public health programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Female sex was found to be an independent predictor of survival to hospital admission from one study from Sweden [ 20 ] which reviewed 529 patients who experienced a cardiac arrest from drowning [ 20 ]. Other studies [ 51 , 52 , 61 ] found no difference in the outcomes between females and males in cardiac arrest from drowning. In Claesson et al [ 20 ] females made up 55% of the study population, compared to a smaller proportion of females in the study populations of the other studies 27% [ 61 ], 35% [ 51 ] and 44% [ 52 ].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Female sex was found to be an independent predictor of survival to hospital admission from one study from Sweden [ 20 ] which reviewed 529 patients who experienced a cardiac arrest from drowning [ 20 ]. Other studies [ 51 , 52 , 61 ] found no difference in the outcomes between females and males in cardiac arrest from drowning. In Claesson et al [ 20 ] females made up 55% of the study population, compared to a smaller proportion of females in the study populations of the other studies 27% [ 61 ], 35% [ 51 ] and 44% [ 52 ].…”
Section: Discussionmentioning
confidence: 92%
“…Other studies [ 51 , 52 , 61 ] found no difference in the outcomes between females and males in cardiac arrest from drowning. In Claesson et al [ 20 ] females made up 55% of the study population, compared to a smaller proportion of females in the study populations of the other studies 27% [ 61 ], 35% [ 51 ] and 44% [ 52 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Drowning was the leading cause of mortality (57%) managed by the BMPM SMUR (58.3% stage 5, 6 and death of Szpilman). This severity is observed in other studies [4,[7][8][9]. Jean-Paul Boudsocq et al, Epidemiology of physician interventions in maritime environment by the Marseille Fire Brigade (BMPM) While adults between ages 45 and 64 were the most commonly affected, the one infant (under age 5) that drowned was also a Szpilman stage 6 [1].…”
Section: Discussionmentioning
confidence: 59%